Microstructure scale modelling of the WC and Co phases plastic behaviour in the WC-Co composite with different cobalt contents and for different temperatures. Comparison of the Drucker-Prager and Mises models. (September 2021) - Agode, K.E.; Wolff, C.; Nouari, M.; Moufki, A.
Abstract: Despite several years of research and development works, the understanding of the tungsten carbide (WC-Co) behaviour under complex thermomechanical loading is not yet complete. Indeed, data is quite rare for the elevated temperatures encountered in the various applications and makes the description of this material a difficult task. In the present work, the elastoplastic behaviour of various grades of WC-Co composites are simulated numerically from room temperature up to 900 °C thanks to the creation of realistic microstructures. This microstructure-level model allows to determine the representative volume element (RVE) considering the two phases tungsten carbide (WC) and cobalt (Co) to reproduce the real macroscopic behaviour of the composite under compression loading. The elastoplastic behaviour of the Co phase has been identified from the literature and the yield criterion of WC phase estimated at different temperatures by the introduction and determination of two temperature functions α 1 ( T ) and α 2 ( T ). The latter represent the dependence of the yield stress and hardening, respectively. A comparison between the von Mises and Drucker-Prager criteria applied to the WC phase has been also discussed. A good agreement is obtained between the numerical simulation results and experimental data. Highlights: A finite element analysis of the elastoplastic behaviour of WC-Co material at the microstructural scale has been developed. A study has also been led to determinate the WC grain minimum number, which is 250 grains. The elastoplastic behaviour of the cobalt and tungsten carbide phases have been extended for temperatures up to 900 °C. Simulations have been performed to predict the stress-strain curves in compression of the composite WC-10.5wt.%Co. A A comparison between the von Mises and Drucker Prager criteria applied to the carbide phase have been discussed.